Fetal nuchal translucency: ultrasound screening for chromosomal defects in first trimester of pregnancy - Nicolaides, K. H.; Azar, G.; Byrne, D.; Mansur, C.; Marks, K. (BMJ, 1992)
OBJECTIVE--To examine the significance of fetal nuchal translucency at 10-14 weeks' gestation in the prediction of abnormal fetal karyotype. DESIGN--Prospective screening study. SETTING--The Harris Birthright Research Centre for Fetal Medicine, King's College Hospital, London. SUBJECTS--827 fetuses undergoing first trimester karyotyping by amniocentesis or chorionic villus sampling. MAIN OUTCOME MEASURE--Incidence of chromosomal defects. RESULTS--The incidence of chromosomal defects was 3% (28 of 827 cases). In the 51 (6%) fetuses with nuchal translucency 3-8 mm thick the incidence of chromosomal defects was 35% (18 cases). In contrast, only 10 of the remaining 776 (1%) fetuses were chromosomally abnormal. CONCLUSION--Fetal nuchal translucency > or = 3 mm is a useful first trimester marker for fetal chromosomal abnormalities.